PEMANFAATAN SOFTWARE OPEN SOURCE â€œRâ€ UNTUK PENELITIAN AGROKLIMAT - Sarvina, Yeli (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2017)
Analysis in agro-climate research often uses long and varied time series data and even involves complex simulation models. Software is required to produce information quickly, precisely, and accurately. Agro-climate research is sometime constrained by the availability proprietary software since cost of proprietary/ licensed software is relatively high. Open source software (OSS) is one solution to overcome this constrain whereas OSS can be used freely. This paper discusses the utilizationÂ ofÂ